1999
DOI: 10.1074/jbc.274.24.16871
|View full text |Cite
|
Sign up to set email alerts
|

RIP3, a Novel Apoptosis-inducing Kinase

Abstract: RIP3 is a novel gene product containing a N-terminal kinase domain that shares extensive homology with the corresponding domain in RIP (receptor-interacting protein) and RIP2. Unlike RIP, which has a C-terminal death domain, and RIP2, which has a C-terminal caspase activation and recruitment domain, RIP3 has a unique C terminus. RIP3 binds RIP through its unique C-terminal segment and by virtue of this interaction is recruited to the tumor necrosis factor (TNF) receptor-1 signaling complex. Previous studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
196
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(209 citation statements)
references
References 32 publications
10
196
1
2
Order By: Relevance
“…Our results on the kinase-independent role of RIPK3 in TNF-mediated apoptosis are in line with early work reporting apoptosis induction upon ectopic expression of KD RIPK3 mutants. 37,48 It was also previously reported that RIPK3 could, directly or indirectly, interact with the prodomain of caspase-8 upon ectopic expression. 37 It is therefore possible that the contribution of RIPK3 to TNF-mediated apoptosis involves another mechanism than ROS production.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our results on the kinase-independent role of RIPK3 in TNF-mediated apoptosis are in line with early work reporting apoptosis induction upon ectopic expression of KD RIPK3 mutants. 37,48 It was also previously reported that RIPK3 could, directly or indirectly, interact with the prodomain of caspase-8 upon ectopic expression. 37 It is therefore possible that the contribution of RIPK3 to TNF-mediated apoptosis involves another mechanism than ROS production.…”
Section: Discussionmentioning
confidence: 86%
“…RIPK3 has emerged as an essential kinase in necroptosis induction [25][26][27] and, as a consequence, RIPK3 repression has become a proof of principle to highlight the contribution of necroptosis in a defined phenotype; although initial reports on RIPK3 indicated that its ectopic expression could also induce apoptosis. 37,38 To investigate whether RIPK3 could contribute to TNF-induced RIPK1-dependent apoptosis, we stimulated immortalized Ripk3 þ / þ and Ripk3 À / À MEFs with TNF þ SM and TNF þ TAK1i. Remarkably, we observed that RIPK3 deficiency provided partial protection to both apoptotic triggers (Figures 5a-d, Supplementary Figure S7).…”
Section: As Shown In Figures 4a-d (And Supplementarymentioning
confidence: 99%
“…Thus, in the context of the apoptotic machinery (the ripoptosome) it appears that, without activating the kinase, dimerization of the RIPKs induces apoptosis, probably via the C terminal domain. 8,9,22 If dimerization of the two different RIPK domains has different outcomes, what determines the mode of cell death? This is most clearly answered by examining the death of Ripk1 À / À cells following dimerization of RIPK3.…”
Section: Discussionmentioning
confidence: 99%
“…21 It is also unclear whether RIPK3 can contribute to apoptosis. Despite some reports to this effect, 8,9,22 RIPK3 has been described as the necroptotic 'switch', implying its activity precipitates necroptosis to the exclusion of apoptosis. [23][24][25] Here, we have directly activated RIP kinases without the confounding effects of multiple signals emanating from the target cell's cytokine receptors, allowing us to define more precisely the functions of RIPK1 and RIPK3.…”
mentioning
confidence: 98%
See 1 more Smart Citation